2022
DOI: 10.1037/edu0000688
|View full text |Cite
|
Sign up to set email alerts
|

App-based morphological training produces lasting effects on word knowledge in primary school children: A randomized controlled trial.

Abstract: Educational Impact and Implications StatementWords can consist of several meaningful parts, or morphemes, such as -ist in guitarist and re-in reuse. Understanding common morphemes helps children infer the meanings of new words. In this study, we tested the effects of working with an educational application (app) focusing on morphemes. Children completed app exercises such as sorting words or pictures according to their meaning, combining morphemes to build words, or identifying the correct word or morpheme to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 114 publications
1
8
0
Order By: Relevance
“…We found lasting effects on students' morphological word knowledge immediately after the training period and 6 months later, aligning with previous findings from the same project (Torkildsen et al, 2021). Specifically, the program increased students' performance on a latent measure of the ability to explain, manipulate, use, and understand words with trained morphemes compared to an active control group working with a math application.…”
Section: The Relative Effectiveness Of the Morphology Programsupporting
confidence: 88%
See 3 more Smart Citations
“…We found lasting effects on students' morphological word knowledge immediately after the training period and 6 months later, aligning with previous findings from the same project (Torkildsen et al, 2021). Specifically, the program increased students' performance on a latent measure of the ability to explain, manipulate, use, and understand words with trained morphemes compared to an active control group working with a math application.…”
Section: The Relative Effectiveness Of the Morphology Programsupporting
confidence: 88%
“…This study employs the same data set as the study by Torkildsen et al (2021) but was preregistered as a separate study in the Open Science Framework (https://doi.org/10. 17605/OSF.IO/TG24F).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of research has shown that morphological knowledge predicts vocabulary, reading fluency and reading comprehension in many languages (James et al, 2021; Manolitsis et al, 2019; McBride‐Chang et al, 2005), and that morphological instruction can enhance children's word knowledge and reading development (e.g., Bowers et al, 2010; Carlisle, 2010; Goodwin & Ahn, 2010; Lyster et al, 2016; Reed, 2008; Torkildsen et al, 2022). The Morphological Pathways Framework introduced by Levesque et al (2021) provides a theoretical model of the mechanisms behind the influence of morphology on other areas of literacy.…”
Section: Introductionmentioning
confidence: 99%